The Effect of Open Unemployment The Effect of Open Unemployment Rate, Inflation Rate, and Investment on Human Development Index (HDI) and Poverty in South Sulawesi Province: The Effect of Open Unemployment Rate, Inflation Rate, and Investment on Human Development Index (HDI) and Poverty in South Sulawesi Province - Nurinsana, Fahirah; Sudirman (ICOR: Journal of Regional Economics, 2024)
Developing countries usually face various problems, such as poverty and unemployment, in other sectors, including employment issues. The poverty depth index in South Sulawesi Province has decreased in the midst of the current COVID-19 pandemic. To overcome poverty, various government methods and strategies are needed that must be resolved first, such as high unemployment, increasing population, high inflation, low economic growth, and so on. The purpose of this research is to find out how unemployment (TPT), inflation rate, and investment affect the human development index (HDI) and poverty in South Sulawesi Province. The type of research used is quantitative research, and the data from this study is secondary data, which is a time series starting from 2006 to 2020. The results of this study indicate that unemployment has a negative and insignificant effect on HDI, inflation rate has a negative and insignificant effect on HDI, investment has a negative and insignificant effect on HDI, unemployment has a positive and significant effect on poverty, the inflation rate has a positive and significant effect on poverty, investment has a negative and significant effect on poverty and HDI has a negative and insignificant effect on poverty